1996
DOI: 10.1021/ie950186o
|View full text |Cite
|
Sign up to set email alerts
|

A Semiempirical Kinetic Model for Dissolution of Colemanite in Aqueous CH3COOH Solutions

Abstract: In this study the dissolution of Colemanite in aqueous acetic acid solutions was investigated in a batch reactor employing the parameters of particle size, solid-to-liquid ratio, and temperature. It was found that the dissolution rate increases with increasing temperature and decreasing solid-to-liquid ratio and particle size. The most effective parameter was particle size with a power of −1.420 after temperature and solid-to-liquid had less effect than the other parameters. The conversion rate increased up to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(31 citation statements)
references
References 3 publications
3
27
0
1
Order By: Relevance
“…(6)) (Alkan and Dogan, 2004;ZareNezhad, 2003), acetic acid (Eq. (7)) (Ekmekyapar et al, 2008;Ozmetin et al, 1996) and citric acid (Eq. (8)) (Ciftci, 2012), was investigated in terms of their B 2 O 3 extraction conditions.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%
“…(6)) (Alkan and Dogan, 2004;ZareNezhad, 2003), acetic acid (Eq. (7)) (Ekmekyapar et al, 2008;Ozmetin et al, 1996) and citric acid (Eq. (8)) (Ciftci, 2012), was investigated in terms of their B 2 O 3 extraction conditions.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%
“…Concerning metal species in elemental form, during leaching experiments oxidation occurs to the divalent state according to reactions (5)- (9) and therefore the solubilization conditions can be predicted from relevant E h -pH diagrams, as presented in …”
Section: Chemistry Of the Solution And Theoretical Behavior Of The Phmentioning
confidence: 99%
“…This behavior could be explained by the fact that as the acid concentration in the medium increases, the apparent rate of product increases and as the product reaches the saturation value near the solid particle; it forms a difficult soluble solid film layer around the particle. Consequently, the dissolution process slows down [9].…”
Section: Effect Of Acid Concentrationmentioning
confidence: 99%
“…Filtration of calcium salts from pregnant solution has an important role in the production of boric acid, since these salts reduce the quality of the boric acid produced and generate environmental pollution. 6,16 Bayca reported that boric acid is currently produced in Turkey by the acid leaching process. In this process, colemanite concentrate is leached with a hot sulfuric acid solution, the result being calcium ions.…”
Section: Introductionmentioning
confidence: 99%